Neurolinguistics Programming Method to Enhance Students’ Reading Interest - Sri Rahmadhani Siregar; Eka Sustri Harida (English Education : English Journal for Teaching and Learning, 2019)
The aim of this research was to investigate if there is a significant effect of neurolingistics programming method into students’ reading interest. Quantitative research was used to conduct the research by divided students into experimental and control class, who were cluster randomly selected. Both classes were given pre-test and post- test to find out whether there is a significance effect of treatment or not. Questionnaire was used to collect the data. The result of the research showed that students who were taught by neurolinguistics programming method were better than those were taught by habitual teachers’ strategy. It is concluded that neurolinguistics programming method gives a significant effect on students’ reading interest. Neurolinguistics programming method is recommended to English teacher to enhance their students’ interest in reading comprehension. From the result of this research, Neurolinguistics programming method is recommended to English teacher to enhance their students’ interest in reading comprehension.